Beyond physiology: Acute effects of side-alternating whole-body vibration on well-being, flexibility, balance, and cognition using a light and portable platform A randomized controlled trial - Faes, Yannik; Rolli Salathé, Cornelia; Herlig, Marina Luna; Elfering, Achim (Frontiers in Sports and Active Living, 2023)
A good body-balance helps to prevent slips, trips and falls. New body-balance interventions must be explored, because effective methods to implement daily are sparse. The purpose of the current study was to investigate acute effects of side-alternating whole-body vibration (SS-WBV) training on musculoskeletal well-being, flexibility, body balance, and cognition. In this randomized controlled trial, participants were randomly allocated into a verum (8.5 Hz, SS-WBV, N = 28) or sham (6 Hz, SS-WBV, N = 27) condition. The training consisted of three SS-WBV series that lasted one-minute each with two one-minute breaks in between. During the SS-WBV series, participants stood in the middle of the platform with slightly bent knees. During the breaks in between, participants could loosen up. Flexibility (modified fingertip-to-floor method), balance (modified Star Excursion Balance Test), and cognitive interference (Stroop Color Word Test) were tested before and after the exercise. Also, musculoskeletal well-being, muscle relaxation, sense of flexibility, sense of balance, and surefootedness were assessed in a questionnaire before and after the exercise. Musculoskeletal well-being was significantly increased only after verum. Also, muscle relaxation was significantly higher only after verum. The Flexibility-Test showed significant improvement after both conditions. Accordingly, sense of flexibility was significantly increased after both conditions. The Balance-Test showed significant improvement after verum, and after sham. Accordingly, increased sense of balance was significant after both conditions. However, surefootedness was significantly higher only after verum. The Stroop-Test showed significant improvement only after verum. The current study shows that one SS-WBV training session increases musculoskeletal well-being, flexibility, body balance and cognition. The abundance of improvements on a light and portable platform has great influence on the practicability of training in daily life, aiming to prevent slip trips and falls at work.